ANALISIS PENERAPAN METODE ACTIVITY BASED COSTING DALAM PENENTUAN TARIF JASA PERNIKAHAN DI MASA PANDEMI (STUDI PADA NOVIE WEDDING) - Irwanto, Sofa Marwa; Puspita, Erna; Sugeng, Sugeng (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
The pandemic period has an impact on changes in the business environment, thereby increasing customer choice in determining the products and services to be used. During this pandemic, the right tariff calculation will help companies stay afloat and compete. The purpose of this study is to analyze the calculation in determining the tariff for wedding services, while the method used is the Activity Based Costing method. Done at a wedding service provider company Novie Wedding. This type of research is descriptive quantitative research. Based on the data obtained, there are two types of service packages. From the results of the study, it is known that the calculation between the conventional method and the ABC method, there is a difference in the calculation of the number of rates for wedding services for each service package offered. The COD package is IDR 55,000 and the New Normal package is IDR 35,000. Then the comparison of the difference obtained from the results of calculations using the conventional method and the ABC method can be used for consideration in determining the selling rate by the Novie Wedding.